2021
DOI: 10.1016/j.optom.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nanoemulsion and non-emollient artificial tears on tear lipid layer thickness and symptoms

Abstract: Purpose Dry eye disease (DED) is often managed with over-the-counter eye drops. This study evaluated the diurnal effects of a single drop of two ocular lubricants (nanoemulsion vs. non-emollient) on tear film lipid layer thickness (LLT) and symptoms of ocular dryness. Subjects were also assessed after 1 month of nanoemulsion eye drop use. Methods Part 1 was a cross-over comparison of a nanoemulsion and a non-emollient eye drop. LLT and dry eye symptoms were measured at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…Relatively rapid and then sustained symptomatic relief occurred at the first month of use with both drops, which is consistent with the outcomes of previous studies with shorter follow up periods. [2,7,8,27,33] In the current study, symptomatic improvement plateaued after Day 30 and at the 6-month time point, both drops demonstrated statistically and clinically significant symptomatic improvements averaging a reduction of 11, 3-and 17-J o u r n a l P r e -p r o o f points in OSDI, DEQ-5 and SANDE scores, respectively. The relatively early onset of superior LWE improvements observed with both drops, which suggests reduced blinkrelated friction at the lid wiper, aligns favourably with the symptomatic improvement.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Relatively rapid and then sustained symptomatic relief occurred at the first month of use with both drops, which is consistent with the outcomes of previous studies with shorter follow up periods. [2,7,8,27,33] In the current study, symptomatic improvement plateaued after Day 30 and at the 6-month time point, both drops demonstrated statistically and clinically significant symptomatic improvements averaging a reduction of 11, 3-and 17-J o u r n a l P r e -p r o o f points in OSDI, DEQ-5 and SANDE scores, respectively. The relatively early onset of superior LWE improvements observed with both drops, which suggests reduced blinkrelated friction at the lid wiper, aligns favourably with the symptomatic improvement.…”
Section: Discussionsupporting
confidence: 53%
“…However, no effects were observed 15 minutes post-instillation, or after a month of four times daily instillation. [27] Other studies have also failed to detect differences in lipid layer thickness minutes to days post-instillation of these or other lipid-based drops. [28][29][30] Reasons for differences might relate to the nature of subjective lipid layer grading which reflects the dynamic distribution profile of the entire interpalpebral lipid layer, [31] rather than an average of absolute measures of lipid thickness calculated over a predefined area.…”
Section: Discussionmentioning
confidence: 99%
“…Because the eye is accessible and can be washed with high concentrations of topical antibiotics, eye drops are usually applied to these surface-associated infections and prevent the devastating complication of endophthalmitis. To delay the emergence of drug resistance, novel ocular nanotherapeutics should decrease the elimination process by enhancing the contact time and improving the bioavailability of nanotherapeutics. , Recently, evidence for nanoemulsions as ocular therapeutics has captured much attention owing to their thermodynamic stability and small particle size . Moreover, PDT as an non-antibiotic treatment has been applied in ocular disease. , …”
Section: Resultsmentioning
confidence: 99%
“…44,45 Recently, evidence for nanoemulsions as ocular therapeutics has captured much attention owing to their thermodynamic stability and small particle size. 46 Moreover, PDT as an non-antibiotic treatment has been applied in ocular disease. 47,48 To explore whether PFH/F-I resists bacteria efficiently in vivo, a rat "scratched cornea" and P. aeruginosa-infected model, which closely resembles keratitis, was designed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“… 26 In addition, nanoemulsion ocular solutions could increase the lipid layer thickness at 10 minutes post-instillation of the emulsion. 27 A recent study investigating tear lipid thickness using the tear film interferometry method found that the tear lipid thickness increased significantly with lipid tear supplements. 28 Therefore, this increase in lipid layer thickness may explain the reduction in tear film evaporation rate and improved tear film stability.…”
Section: Discussionmentioning
confidence: 99%